Incidence of scoliotic posture in school screening of urban children and adolescents: the case of Poznań, Poland - Maciałczyk-Paprocka, Katarzyna; Dudzińska, Joanna; Stawińska- Witoszyńska, Barbara; Krzyżaniak, Alicja (Anthropological Review, 2018)
Postural defects including scoliotic posture constitute one of the most frequently observed health problems in school-aged children. The incidence of this multifactorial condition has been observed to increase recently. The aim of the study was to assess the incidence of scoliotic posture in primary and secondary school students living in a large city. The sample consisted of 1,325 boys and 1,355 girls, aged 6 to 18, living in the city of Poznań. Their postures were assessed through skilled visual inspection method based on the criteria delineated by Wiktor Dega. Additionally, measurements of scoliotic deformities were taken using the Bunnell’s scoliometer. It was found that the incidence of scoliosis assessed on the basis of Dega’s postural defect chart amounted in total to 14.6% in boys and 17% in girls. No substantial differences between boys and girls in particular age categories were found. Scoliometer examination appeared to be a more accurate method for screening scoliosis and revealed higher incidence of this condition in total and both in boys and girls as compared to the visual screening method. The contractures which may lead to scoliotic posture appeared most frequently in the knee joints, both in boys and in girls. The incidence of lateral spinal curvatures was related to age and increased with age. Scoliometer proved to be a more effective tool in detecting lateral spinal curvatures and should be more widely used in school healthcare.